When Love Just Ends: An Investigation of the Relationship Between Dysfunctional Behaviors, Attachment Styles, Gender, and Education Shortly After a Relationship Dissolution - Civilotti, Cristina; Dennis, John Lawrence; Acquadro Maran, Daniela; Margola, Davide (Frontiers in Psychology, 2021)
Much is known about the long-term consequences of separation and divorce, whereas there is a paucity of studies about the short-term consequences of such experiences. The present study investigates the adoption of dysfunctional behaviors (e.g., insistent telephone calls and text messages, verbal threats, sending unwanted objects) shortly after a relationship dissolution. 136 participants who declared to have been left by their former partner in the previous six months were included in the study (females: n = 84; males: n = 52; mean age = 30.38; SD = 4.19). Attachment styles were evaluated as explanatory variables when facing a relationship dissolution, in connection with a set of (1) demographic variables (gender, education, and current marital/relationship status), (2) dysfunctional behaviors, and (3) motivations at the basis of those behaviors. Results showed that a secure or dismissing attachment style, a higher education, and currently married (but awaiting separation) status were protective factors in adopting such dysfunctional behaviors, while the preoccupied and fearful-avoidant subjects, especially females, tended to adopt dysfunctional behaviors (i.e., communication attempts and defamation) and reported fear of abandonment and need for attention as underlying motivations. Future study on longitudinal aspects of the relationship dissolution processes is needed to have deeper insights into this phenomenon. The current study sheds light on the relationship between adult attachment styles and the motivations behind the adoption of dysfunctional behaviors after a relationship dissolution.